Facial features extraction using active shape model and constrained local model: a comprehensive analysis study - Iqtait, Musab; Alqaryouti, Marwan Harb; Sadeq, Ala Eddin; Abuowaida, Suhaila; Issa, Abedalhakeem; Almatarneh, Sattam (IAES International Journal of Artificial Intelligence (IJ-AI), 2025)
Human facial feature extraction plays a critical role in various applications, including biorobotics, polygraph testing, and driver fatigue monitoring. However, many existing algorithms rely on end-to-end models that construct complex classifiers directly from face images, leading to poor interpretability. Additionally, these models often fail to capture dynamic information effectively due to insufficient consideration of respondents' personal characteristics. To address these limitations, this paper evaluates two prominent approaches: the constrained local model (CLM), which accurately extracts facial features depending on patch experts, and the active shape model (ASM), designed to simultaneously extract the appearance and shape of an object. We assess the performance of these models on the MORPH dataset using point to point error as evaluation metrics. Our experimental results demonstrate that the CLM achieves higher accuracy, while the ASM exhibits better efficiency. These findings provide valuable insights for selecting the appropriate model based on specific application requirements.